Analysis of Unplanned Postoperative Admissions to the Intensive Care Unit. (August 2017) - Quinn, Timothy D.; Gabriel, Rodney A.; Dutton, Richard P.; Urman, Richard D.
Purpose: To investigate factors associated with unplanned postoperative admissions to the intensive care unit (ICU). Methods: Data from the National Anesthesia Clinical Outcomes Registry (NACOR) were analyzed. We performed univariate and multivariate logistic regression to identify patient- and surgery-specific characteristics associated with unplanned postoperative ICU admission. We also recorded the prevalence of Current Procedural Terminology (CPT) and International Classification of Diseases, ninth revision ( ICD-9 ) billing codes and outcomes for unplanned postoperative ICU admissions. Results: Of 23 341 130 records in the database, 2 910 738 records met our inclusion criteria. A higher American Society of Anesthesiologists physical status (ASA PS) class, case duration greater than 4 hours, and advanced age were associated with a greater likelihood of unplanned ICU admission. Vascular and thoracic surgery patients were more likely to have an unplanned ICU admission. The most common CPT and ICD-9 codes involved repair of femur/hip fracture, bowel resection, and acute postoperative pain. Large community hospitals were more likely than university hospitals to have unplanned postoperative ICU admissions. Patients in the unplanned postoperative ICU admission group were more likely to have experienced intraoperative cardiac arrest, hemodynamic instability, or respiratory failure and were more likely to die in the immediate perioperative period. Conclusion: Our study is the first diverse analysis of unplanned postoperative ICU admissions in the literature across multiple specialties and practice models. We found an association of advanced age, higher ASA PS class, and duration of procedure with unplanned ICU admission after surgery. Surgical specialties and procedures with the most unplanned ICU admissions could be areas for quality improvement and clinical pathways in the future.